Supply Chain in Insurance of High-Tech Companies: Formation Characteristics - Valeriy Prasolov; Seymur Hajiyev; Zarema Sharifyanova; Yuliia Diachkova (International Journal of Supply Chain Management, 2020)
Abstract— This article was aimed at forming an idea of companies’ portfolios applying high technologies in the process of modern supply chain insurance business digitalization. For this aim, the analysis of Russian and Azerbaijan insurance markets and the dynamics of their gradual implementation of online technologies was carried out. To compile an objective picture of the current market situation, two insurance firms, namely, AlfaStrakhovanie and Mango Insurance Company, were selected for the research. As part of the analysis, the study examined the supply chain insurance structure of the AlfaStrakhovanie Company. Within the present research, the features of its regulation and diversification were highlighted. Moreover, the study outlined the work specifics of new insurance companies and InsurTech startups in domestic realities. Despite higher possibilities of supply chain disruptions, enterprises in APAC exhibit lesser investment in the supply chain industry because of their lack of knowledge on the same and their reluctance to pay high premiums. The obtained results were based on the Markowitz portfolio optimization model and allowed creating the optimal supply chain structure of the insurance company’s portfolio, taking into account the risks associated with the use of modern technologies.